Price Liberalization, Money Growth, and Inflation During the Transition to a Market Economy - Hernandez-Cata, Ernesto (Washington, D.C. : International Monetary Fund, 1999)
This paper examines the influence of economic liberalization and monetary growth on inflation during the transition from central plan to market. It concludes that price decontrol had a substantial, one-time effect on the price level but no lasting effect on inflation; that economic liberalization broadly defined may have helped dampen price increases; and that monetary expansion has been the fundamental determinant of inflation in the region. The paper also finds that the intensity of liberalization has been related to geographic proximity to market economies, to the size of the underground economy, and to the degree of political freedom.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet